Standardization of pre –sowing seed treatments with selected organic manures on growth, yield and nutritive quality parameters of beetroot (Beta vulgaris L.) under Prayagraj zone - Anindita Sikda,; Bazil Avinash Singh,; Prashant Kumar Rai,; Vaidurya Pratap Sahi, (Annals of Agricultural Research, 2025)
With a view to find out the effect of pre – sowing seed treatment on growth, yield and nutritive quality on beetroot (Beta vulgaris L.) seeds, experiment was conducted during Rabi 2023 – 2024 at Central Research Field, Department of Genetics and Plant Breeding, SHUATS, Prayagraj (UP), India. The seeds of variety Ruby Queen of beetroot were evaluated under ten priming treatments viz. T0: Untreated (control), T1: Farmyard Manure (FYM) 8% @ 12 hours, T2: Poultry Manure (PM) 8% @ 12 hours, T3: Goat Manure (GM) 8% @ 12 hours, T4: Vermicompost 8% @ 12 hours, T5: Mustard Cake 8% @ 12 hours, T6: Groundnut Cake 8% @ 12 hours, T7: Neem cake 8% @ 12 hours, T8: Horn meal 8% @ 12 hours, T9: Bone meal 8% @ 12 hours and T10: Diatomaceous Earth Powder (DEP) 8% @ 12 hours in Randomized Block Design and replicated thrice. Maximum growth and yield parameters were observed when seeds were primed with T1: FYM followed by T5: Mustard cake and T7: Neem cake. Among the treatments T0: Untreated (control) recorded minimum. Thus, among all the priming treatments T1: FYM 8% @ 12 hours was found to be the best priming treatment.